The Effectiveness of Cognitive Behavioral Therapy (CBT) To Decreased Depression in Woman Patients with Cancer included cervical cancer and breast cancer - Dwi Fitriyanti; Mardiyono Mardiyono; Yuriz Bakhtiar (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
The highest cancers in Indonesia in women are breast cancer and cervical cancer. Both are the most common cancers in women and the highest cause of death in women. Some woman patients with newly diagnosed of breast cancer or cervical cancer will experience depression. most patients newly diagnosed with cancer, less than 6 months reported a feeling of depression of 91.4%. An effective intervention to reduce the level of depression is to provide cognitive behavioral therapy (CBT) interventions. CBT is a psychotherapy recommended for treating depression in patients with breast cancer and cervical cancer. The objective of this study to review the effects of CBT on decreasing depression in woman patients with cancer including cervical cancer and breast cancer. This study is a systematic review. We search articles from EBSCOhost, Google Scholar, Pubmed, and Science Direct database which published from 2008 till 2018. RCTs are included in this review. Four RCTs included in this study. CBT interventions are carried out differently for each article, in general, each session is given for 60-90 minutes with a different number of sessions. Outcome measured in 3 articles was more than one variable (not only depression) and one article only measured the level of depression. Cognitive behavioral therapy can be used for woman patients with breast cancer and cervical cancer who are depressed. Future research to the effectiveness of CBT in reducing depression in woman patients specifically in newly diagnosed with cervical cancer is needed to confirm the evidence